Adhesive joining of copper using nano-filler composite adhesive. (22nd March 2016) - Ghosh, P.K.; Patel, Avantak; Kumar, Kaushal
Abstract: Effect of well dispersed nano particles filled epoxy based adhesive prepared by an innovative ultrasonic dual mixing on lap joint of copper was investigated. Effect of mechanical and chemical treatment of copper substrate on lap shear strength of its adhesive joint produced by using composite adhesive containing 5, 10, and 15 wt.% TiO2 particles of size 30 ± 5 nm. The lap shear strength of the joint was also studied as a function of bond line thickness of the adhesive. Fracture behavior of the joint under the lap shear loading has also been studied. Characteristics of the nano particles filled epoxy adhesive joints were compared with the adhesive joints of neat epoxy. Adhesive joint of chemically treated copper shows relatively higher lap shear strength than that of the mechanically treated copper while the joint of composite adhesive shows considerably higher strength as compared to that of the neat adhesive. Graphical abstract: Highlights: Adhesive joints on copper substrate were prepared by UDM processed TiO2 nano-filler epoxy adhesive. Lap shear strength of adhesive joints on mechanically and chemically treatment copper substrate was investigated. Bond line thickness of adhesive joint on copper substrate was optimized with its lap joint strength. Adhesive joint on chemically treated copper substrate has superior properties as compared with mechanically treated.